On the use of non-orthogonal multiple access for V2V message dissemination - Benabdallah, Fairouz; Hamza, Abdelkrim; Becherif, Mohamed (IET intelligent transport systems, 2019)
Vehicular networks are characterised by a high density of nodes moving at a high speed and accessing the medium simultaneously which enlarges the interference, decreases the network throughput and spectral efficiency. That increases the challenge of designing a reliable communication scheme to handle the particular characteristics of this network and ensure user fairness. Here, a new vehicle-to-vehicle communication scheme is proposed. It consists of using particular vehicles (selected upon their position) to disseminate the message using non-orthogonal multiple access technique. Power domain NOMA allocates a great amount of power to the vehicle in poor conditions, which enhances the system power control; improve throughput and user fairness in comparison with the OMA-based IEEE 802.11p standard. A log-normal shadowing is considered to model the propagation channel. The simulation results show that considering a channel model where severe conditions of signal propagation are present, a more advanced receiver designs have to be proposed on the subject of channel estimation and equalisation to mitigate channel effect on the received data. However, even in a harsh fading environment, NOMA outperforms OMA in terms of network throughput, spectral efficiency, and user fairness, which makes it a very promising solution for future development of vehicular communication systems.